2011
DOI: 10.3390/s110302982
|View full text |Cite
|
Sign up to set email alerts
|

Application of V2O5/WO3/TiO2 for Resistive-Type SO2 Sensors

Abstract: A study on the application of V2O5/WO3/TiO2 (VWT) as the sensitive material for resistive-type SO2 sensor was conducted, based on the fact that VWT is a well-known catalyst material for good selective catalytic nitrogen oxide reduction with a proven excellent durability in exhaust gases. The sensors fabricated in this study are planar ones with interdigitated electrodes of Au or Pt. The vanadium content of the utilized VWT is 1.5 or 3.0 wt%. The resistance of VWT decreases with an increasing SO2 concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 24 publications
(33 reference statements)
3
24
0
1
Order By: Relevance
“…It was found that at higher concentration, the relation between SO 2 concentration to the first discriminant function was not linear anymore, but more exponential. This observation that the linear correlation changed into exponential at high SO 2 concentrations appeared to agree with some previous studies on other SO 2 sensors [25,26]. However, in some groups, it was observed that the increase was very sharp at higher concentrations.…”
Section: Performance Test In Desulphurization Pilot Plant Unitsupporting
confidence: 79%
“…It was found that at higher concentration, the relation between SO 2 concentration to the first discriminant function was not linear anymore, but more exponential. This observation that the linear correlation changed into exponential at high SO 2 concentrations appeared to agree with some previous studies on other SO 2 sensors [25,26]. However, in some groups, it was observed that the increase was very sharp at higher concentrations.…”
Section: Performance Test In Desulphurization Pilot Plant Unitsupporting
confidence: 79%
“…Previous studies on Au-based sensors [3,27] have also demonstrated the potential of Au as sensing layer for SO 2 sensors. For all three catalytic metals, it was possible to determine the presence of SO 2 with normal static operation.…”
Section: Static Operationmentioning
confidence: 99%
“…Liquid electrochemical cells cannot operate in high humidity and high temperature conditions [1]. Metal oxide sensors usually are not the best choice in environments with low and changing concentration of oxygen [2,3]. Optical detection such as FTIR is relatively more expensive than chemical sensors [4].…”
Section: Introductionmentioning
confidence: 99%
“…6)9) To the best of our knowledge, there are only a few papers reporting on SO 2 19) In this study, we varied the vanadium oxide concentration between 1.5 and 3.0 wt % and the electrode materials between Pt and Au and measured the potential changes when exposed to SO 2 and/or other gases in detail. As a result, it was found out that for the SO 2 response the electrode materials play a more crucial role.…”
Section: Introductionmentioning
confidence: 99%